Analisis Pengaruh Metode AIDA (attention, interest, desire, action) terhadap Keputusan Pembelian Fast Food Berlabel Halal pada Mahasiswa FAI UMSU - Mardiah, Ulfa; Rahmayati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to find out how consumer purchasing decisions for fast food products labeled halal are influenced by the AIDA (attention, interest, desire, action) method applied. As a marketing strategy, the AIDA approach is used to determine how much consumer attention, interest, desires, and behavior can influence the decision to buy fast food that has received halal certification. This research used a quantitative approach by distributing questionnaires to 100 respondents from 925 FAI UMSU students. The sample collected in this research was through purposive sampling, meaning that the sample was based on certain criteria, namely FAI UMSU Stambuk students 2020–2023. The research results showed that simultaneously, the variables attention, interest, desire, and action influenced the decision to purchase halal-labeled fast food. Based on the coefficient of determination, the AIDA approach influences 73.1% of decisions to purchase fast food labeled halal. The remaining 26.9% is influenced by factors not included in the research model